2011
DOI: 10.1029/2010jd015197
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends of the tropical hydrological cycle inferred from Global Precipitation Climatology Project and International Satellite Cloud Climatology Project data

Abstract: Scores of modeling studies have shown that increasing greenhouse gases in the atmosphere impact the global hydrologic cycle; however, disagreements on regional scales are large, and thus the simulated trends of such impacts, even for regions as large as the tropics, remain uncertain. The present investigation attempts to examine such trends in the observations using satellite data products comprising Global Precipitation Climatology Project precipitation and International Satellite Cloud Climatology Project cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
117
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(141 citation statements)
references
References 67 publications
22
117
0
Order By: Relevance
“…But a number of studies have reached an opposite conclusion: that as SST increases the tropical circulations, especially the Walker Cell, reduces intensity (e.g., Vecchi et al 2006;Vecchi and Soden 2007). We will return to this issue later noting that a number of other papers (e.g., Zhou et al 2011;Meng et al 2011) support a more vigorous tropical circulation, in accord with the conclusions reached in the present study.…”
Section: Constancy Of the Area Of The Dynamic Warm Pool (Dwp)supporting
confidence: 78%
See 2 more Smart Citations
“…But a number of studies have reached an opposite conclusion: that as SST increases the tropical circulations, especially the Walker Cell, reduces intensity (e.g., Vecchi et al 2006;Vecchi and Soden 2007). We will return to this issue later noting that a number of other papers (e.g., Zhou et al 2011;Meng et al 2011) support a more vigorous tropical circulation, in accord with the conclusions reached in the present study.…”
Section: Constancy Of the Area Of The Dynamic Warm Pool (Dwp)supporting
confidence: 78%
“…These differences in warming may explain differences in static stability that may help explain a reduction or acceleration of the large-scale tropical circulations. Zhou et al (2011) use data sets independent of the reanalysis products (the Global Precipitation Climatology Program: GPCP, Adler et al 2003, and the International Satellite Cloud Climatolgy Progrect: ISCCP, Rossow and Schiffer 1999) to determine the changes occurring in the Walker and Hadley cells. In agreement with Clement (2005, 2006) they find an intensification of the major tropical circulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of the GCM results over the Western Pacific monsoon region by Smith et al [2012] suggested that these were reasonably consistent with a mechanism which causes relatively dry areas to become drier and relatively wet areas to become wetter, the so-called "rich-get-richer" mechanism [Chou et al, 2009]. Observations also indicate that this mechanism can also explain recent trends in large-scale rainfall patterns [Zhou et al, 2011;Wang et al, 2012]. The CCAM projections are consistent with this mechanism since, spatially, they indicate increases over the relatively wet mountain slopes during DJF (Figures 8 and 9) and decreases over the relatively dry mountains during JJA.…”
Section: Discussionmentioning
confidence: 72%
“…We conclude that the influence of the ALTR on aerosol forcing may be significant, but it is probably small compared to other influences. Particularly important in this respect are changing spatial distributions of aerosol (precursor) emissions and transport routes (Bellouin et al, 2011;Zhang et al, 2007;Carslaw et al, 2010;Zhou et al, 2011), and changes in the aerosol activation efficiency. We present suggestions for model experiments involving idealized aerosol-like tracers that may help to quantify the separate influences on aerosol lifetime and assess their relevance for aerosol-climate simulations.…”
Section: Summary and Discussionmentioning
confidence: 99%